INSULT CASE OF LEONARDO DA VINCI'S "THE LAST SUPPER" PAINTING AT THE PARIS 2024 OLYMPICS FROM A CHRISTIAN PERSPECTIVE - Hadi, Nathanael Yitshak; Setiawan , Iwan; Mariana , Cornelia; Emannuel , Joshua (Relinesia: Jurnal Kajian Agama dan Multikulturalisme Indonesia, 2024)
This study explores the incident of religious desecration that occurred during the opening ceremony of the Paris 2024 Olympics, where a parody of Leonardo da Vinci’s painting “The Last Supper” depicted Jesus Christ as an obese woman and his disciples as members of the LGBTQ community. The research aims to analyze the impact of this event from a Christian perspective, particularly concerning freedom of expression, religious tolerance, and cultural representation theory. This research was conducted in response to the global controversy sparked by religious desecration at an international event like the Olympics. The author seeks to understand how this event was perceived by the Christian community and how it influenced interfaith dialogue and tolerance at a global level. The primary objective of this study is to analyze the offense against the “The Last Supper” painting from a Christian viewpoint, utilizing theoretical frameworks of freedom of expression, religious tolerance, and cultural representation theory. The study also aims to explore how religious representation in global events can influence public perception and ignite discussions on the importance of respecting religious symbols. The research finds that although freedom of expression is a fundamental right in democratic societies, it must be balanced with social responsibility. The incident at Paris 2024 demonstrates that culturally insensitive representations of religious beliefs can trigger strong reactions and lead to conflict. From a Christian perspective, the importance of forgiveness and love in responding to religious insults is emphasized, as well as the need for interfaith dialogue and education to promote tolerance and peace. These findings are crucial as they highlight the need for caution in religious representation at global events to avoid tensions and promote peace. This study also contributes to the broader discussion on the limits of freedom of expression in relation to social responsibility and the importance of education in building interfaith tolerance.